2020
DOI: 10.1155/2020/8036109
|View full text |Cite
|
Sign up to set email alerts
|

Striae Gravidarum, Acne, Facial Spots, and Hair Disorders: Risk Factors in a Study with 1284 Puerperal Patients

Abstract: Objective. To determine the prevalence of skin changes during pregnancy and to relate their occurrence to specific factors in a population of south Brazil. Methods. A cross-sectional analytical study was carried out with 1284 puerperal patients. A questionnaire about skin changes during pregnancy was developed and applied by the authors to all puerperal women admitted in a tertiary hospital in south Brazil. Results. The appearance of striae during pregnancy was reported by 633 women (49.5%) and had a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
4
1
3
Order By: Relevance
“…been described mainly in the first trimester. However, in our study, the onset of this change was more prevalent in the third trimester, which may be explained by the greater weight gain [11,12].…”
Section: Melasmacontrasting
confidence: 69%
See 2 more Smart Citations
“…been described mainly in the first trimester. However, in our study, the onset of this change was more prevalent in the third trimester, which may be explained by the greater weight gain [11,12].…”
Section: Melasmacontrasting
confidence: 69%
“…This fact is associated with the development of melasma and palmar erythema during the first trimester of pregnancy, reported by 25% of patients. Finally, excessive weight gain, which occurred in 31.2% of patients, is related to the occurrence of stretch marks and worsening of acne during pregnancy [11,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the risk factors most linked to their appearance, there are young age at pregnancy, 1,9,10,[15][16][17][18][19][20][21][22][23][24] the fact that it is the first pregnancy, 21,25 a large abdominal circumference before pregnancy, 13,17,19 high body mass index both before pregnancy, 4,9,10,13,16,18,20,21,23,24,26 and during pregnancy, 1,9,13,[18][19][20][21]27,28 previous presence of other striae, 14,16,17,20,25 excessive weight gain during pregnancy, 1,15,[17][18][19][21][22]…”
Section: Introductionmentioning
confidence: 99%
“…Acne vulgaris is a chronic dermatologic condition that affects people during pregnancy and lactation. While epidemiologic data are limited, cross-sectional and survey studies have demonstrated that up to 43% of people experience acne during pregnancy [1][2][3].…”
Section: Introductionmentioning
confidence: 99%